Lung-gut axis, intestinal microbiota, and pulmonary fibrosis: mechanisms and therapeutic potential - Yang, Jihao; Wang, Junwen; Li, Jia; Yang, Shuo (Frontiers in Microbiology, 2025)
Pulmonary fibrosis (PF) is a progressive and life-threatening interstitial lung disease with irreversible lung function loss. The bidirectional interaction between respiratory and gut microbiota mediated by the “lung-gut axis” has emerged as a core regulatory link in PF pathogenesis. This review integrates clinical and preclinical data to systematically clarify the association between microbiota dysbiosis and PF. Clinical evidence shows that PF patients (including idiopathic pulmonary fibrosis, silicosis, and coal workers’ pneumoconiosis) exhibit reduced pulmonary microbiota diversity, increased pro-inflammatory microbial abundance, and altered gut microbiota composition. Preclinical studies using bleomycin or silica-induced PF models confirm consistent microbiota changes and abnormal metabolites. Further, five core pathophysiological mechanisms (immune dysregulation, gut-lung barrier dysfunction, sustained activation of Type 2 epithelial-mesenchymal transition, autophagy modulation, and alveolar epithelial cell apoptosis mediated by microbial peptides) explain how microbiota alterations drive PF progression. Key microbial mediators (e.g., tryptophan metabolites, short-chain fatty acids, lipopolysaccharide, bile acid metabolites) exert bidirectional regulatory effects on PF through synergistic or antagonistic interactions. Additionally, microbiota-targeted strategies such as probiotic/prebiotic intervention, fecal microbiota transplantation, dietary adjustment, and antibiotics have shown experimental anti-fibrotic efficacy. This review highlights the gut microbiota as a potential therapeutic target for PF, while discussing current challenges (e.g., unclear causal relationship, lack of standardized intervention protocols) and future research directions, providing a new framework for PF mechanism research and clinical intervention.